The Influence of Service Quality, Price and Location on Tourist Satisfaction with Tourist Loyalty as An Intervening Variable in Regis Jaya Coffee Village West Lampung Regency - Mubarokah, Zakiatul; Andala Rama Putra Barusman (The Es Economics and Entrepreneurship, 2025)
This study uses tourist loyalty as an intervention variable in Kampung Kopi Rigis Jaya to examine the location. Price. And service quality affects visitor satisfaction. This study collects data using a survey method and a quantitative approach. A purposive sampling strategy combined with a non-probability sampling technique was used to choose the 250 respondents from the research sample. The study's findings demonstrated that neither visitor loyalty nor satisfaction was significantly impacted by service quality. On the other hand. Visitor satisfaction is greatly affected by price and location. Visitor loyalty is significantly impacted by tourist satisfaction. The understanding of the relationship between factors that influence visitor satisfaction and loyalty in community-based tourist destinations particularly Kampung Kopi Rigis Jaya which has not received much attention in prior research is an original contribution of this study. This set of analyses serves as a foundation for creating a plan to raise destination quality by emphasizing location and cost considerations without sacrificing service quality.